MENDUT AND PAWON TEMPLES TOURISM DEVELOPMENT MODEL IN MAGELANG REGENCY - Brata, Elsa Aulia (Universitas Negeri Semarang, 2019)
Magelang Regency had the highest tourism revenue in Central Java. Mendut and Pawon temples include cultural tourism. But in recent years Mendut and Pawon temple tourism revenues did not meet the target. The purpose of this study was to analyze tourist preferences towards Mendut and Pawon Temple cultural attractions, analyze the development strategies that need to be carried out by the Magelang District Government in the development of Mendut and Pawon Temple cultural tourism, and analyze alternative development models of Mendut and Pawon Temples. The population in the study were tourists who visited Mendut and Pawon temple attractions. The number of research samples was 100 tourists and 2 keypersons and were taken purposively. Data collection methods use questionnaires and interviews. The results showed that analysis of the tourist preferences of Mendut Temple was the best aspect of location comfort while Candi Pawon was the best aspect of accessibility, the development strategies of Mendut and Pawon temples in the Matrix Grand Strategy are both in quadrant 1, there are alternative development models of Mendut and Pawon temples that involve the community. Implications of the research of this study is the existence of collaboration between relevant agencies to develop both development and tourism to attract tourists, in addition to the promotion of Mendut and Pawon Temple cultural tourism was again enhanced. Kabupaten Magelang memiliki pendapatan wisata tertinggi di Jawa Tengah. Candi Mendut dan Pawon termasuk wisata budaya. Namun dalam beberapa tahun terakhir pendapatan pariwisata Candi Mendut dan Pawon tidak memenuhi target. Tujuan dari penelitian ini adalah untuk menganalisis preferensi wisatawan terhadap objek wisata budaya Candi Mendut dan Pawon, menganalisis strategi pengembangan yang perlu dilakukan oleh Pemerintah Kabupaten Magelang dalam pengembangan wisata budaya Candi Mendut dan Candi Pawon, serta menganalisis model pengembangan alternatif Candi Mendut dan Pawon. Populasi dalam penelitian ini adalah wisatawan yang mengunjungi objek wisata Candi Mendut dan Pawon. Jumlah sampel penelitian adalah 100 wisatawan dan 2 keypersons dan diambil secara sengaja. Metode pengumpulan data menggunakan kuesioner dan wawancara. Hasil penelitian menunjukkan bahwa analisis preferensi wisatawan dari Candi Mendut adalah aspek terbaik dari kenyamanan lokasi sedangkan Candi Pawon adalah aspek terbaik dari aksesibilitas, strategi pengembangan candi Mendut dan Pawon dalam Matriks Grand Strategy keduanya berada di kuadran 1, ada model pengembangan alternatif candi Mendut dan Pawon yang melibatkan masyarakat. Implikasi dari penelitian penelitian ini adalah adanya kolaborasi antara instansi terkait untuk mengembangkan pembangunan dan pariwisata untuk menarik wisatawan, selain promosi wisata budaya Candi Mendut dan Candi Pawon pun kembali ditingkatkan.